Antiphospholipid syndrome management: a 2023 update and practical algorithm-based approach. Issue 3 (2nd May 2023) - Ambati, Amala; Knight, Jason S.; Zuo, Yu
Abstract : Purpose of review: Antiphospholipid syndrome (APS) is an acquired thrombo-inflammatory disease that has morbid and sometimes devastating effects on patients and their families. This review will discuss the most recent international societal treatment guidelines and propose practical management algorithms for various APS sub-types. Recent findings: APS represents a disease spectrum. Although thrombosis and pregnancy morbidities are traditional hallmarks of APS, a variety of extra-criteria clinical phenotypes can often be seen, which makes clinical management more challenging. Primary APS thrombosis prophylaxis should take a risk-stratified approach. Although vitamin K antagonists (VKAs) or heparin/low molecular weight heparin (LMWH) remain the preferred treatment for secondary APS thrombosis prophylaxis, some international society guidelines support the use of direct oral anticoagulants (DOACs) in certain circumstances. Careful monitoring and individualized obstetric care with the use of aspirin and heparin/LMWH will improve pregnancy outcomes among pregnant individuals with APS. Treatment of microvascular and catastrophic APS remains challenging. While the addition of various immunosuppressive agents is often utilized, further systemic evaluations of their use are warranted before definitive recommendations can be made. Several new therapeutic strategies are on the horizon that might enable more personalized and targeted APS management in the near future. Summary: Although the knowledge of APS pathogenesis has grown in recent years, the management principles and strategies are largely unchanged. There is an unmet need for evaluating pharmacological agents, beyond anticoagulants, that target diverse thromboinflammatory pathways.